MAPY MYŚLI JAKO NARZĘDZIE BADANIA REPREZENTACJI SPOŁECZNYCH WIELOJĘZYCZNOŚCI – PRZYPADEK PRZYSZŁYCH NAUCZYCIELI JĘZYKA FRANCUSKIEGO - Szymankiewicz, Krystyna; Kucharczyk, Radosław (Neofilolog, 2018)
Mind mapping is primarily a learning technique based on creating pictorial notes (Buzan 2003). In the present article, mind maps were used as a tool for the study of social representations, so as to investigate a broad spectrum of ideas, beliefs, and values related to multilingualism. The study involved a group of French Philology students training to become teachers of the French language, and its aim was to determine the extent to which their initial representations of multilingualism were consistent with the theoretical assumptions of the Council of Europe’s language policy. This policy encourages teachers of foreign languages to develop multilingual competence among students. The analysis of mind maps and the transcription of the group interview leads to the conclusion that the respondents show some areas of ignorance and stereotypical beliefs that should be reflected upon in the course of their further education preparing them to the teaching profession.